INFLUENCE OF OVER-SPEED PRELOADING ON THE FATIGUE PERFORMANCE OF IMPELLER - WANG JianNan; YAO YuHua; YANG ShuHua; XIAO ZhongHui; GUAN ZhenQun (Jixie qiangdu, 2017)
Over-speed preloading is one of the important parts in the process of impeller manufacturing,it is a method of checking the impeller’s quality and a subtle strengthen treatment. To explain the mechanics principle of over-speed preloading,finite element models of the impeller are established and then we simulate the process of the over-speed preloading. Firstly,an elastic-plastic analysis is carried out on the semi-open impeller,and the results show that there will be residual stress generated in the high stress regions after preloading,which can reduce the maximal stress produced in the later normal loading. Secondly,analysis of the fatigue life of the semi-open impeller at two different conditions of the starting and stopping and the speed rotating is accomplished through FE-SAFE. By contrast with the results of processing with and without over-speed preloading,we can see that the treatment of over-speed preloading can improve the fatigue life of impeller in a great extent. Moreover,over-speed preloading can also avoid the occurrence of fatigue damage in some conditions of impeller’s speed rotating. Finally,fatigue analysis has been done for closed impeller in a variety of different loading conditions. The results show that the impeller treated with over-speed preloading can resist larger aerodynamic load and avoid fatigue damage.